Relationship of Mother Behavior Against Dental Caries Incidence in Toddler at Putra Sentosa Early Childhood - Ajeng Nindya Cahyaningrum (Universitas Airlangga, 2017)
Dental caries are most often found in under five years children aged 3-5 years. Parents, especially mothers, play an important role in preventive measures, namely the maintenance of dental and oral health of toddlers properly. This study aims to analyze the relationship between maternal behavior about oral health and dental caries incidence in Putra Sentosa Early Childhood / Preschool. This research is analytic research with a case-control study design. The total sample studied was 110 respondents with a ratio of 1: 1 in the case and control groups. Sampling using a simple random sampling technique. Data analysis using the Chi-square test. The results showed that most of the mothers had low knowledge (57.4%), low attitude (62.5%), and unfavorable actions (58.8%) towards the dental and oral health of toddlers. The level of maternal knowledge (p = 0.023; OR = 4.04; 95% CI = 1.154 - 14.164), maternal attitudes (p = 0.016; OR = 3.33; 95% CI = 1.235 - 8.997), and maternal actions (p = 0.016; OR = 4.00; 95% CI = 1,250 - 12,804) have a significant relationship to the incidence of dental caries in children aged 3-5 years. The conclusion of this study is that there is a relationship between knowledge, attitudes, and actions of mothers about oral health on dental caries events in children under five. Health workers and related cross-sector are advised to conduct training and counseling for parents, especially mothers, regarding the maintenance of dental health and toddlers' mouth which includes understanding, benefits, prevention, and diseases that can be prevented by dental and oral health care.